Do U Dy Grudy ao Cantares: as vozes e os acordes da moderna canção popular em Teresina (1973-1988) - Medeiros, Hermano Carvalho (2020)
This thesis proposes to analyze the emergence of what I understand as the modern Brazilian popular music produced in Teresina, capital of Piauí. I will try to narrate the trajectory of a group of composers, performers and musicians who considered the song of the city not only as an object of entertainment or aesthetic appreciation, but also as a vehicle of critical positioning before the cultural, political and social issues of their time. In the 1970s this generation of artists began to produce their spaces and their musical dynamics, period in which Piaui capital went through a modernizing outbreak whose developments were felt in the universe of the arts. Thus, the first collective rehearsals of musical performances came up inspired by a tropicalist and countercultural language that, subsequently, yielded their fruits. Between the late seventies and early eighties began to sprout a series of shows mirrored in the mold of the performances of the great stars of the national songbook, placing the music produced in Teresina in a privileged place in the culture of Piaui. This event made it possible for the State to create a specific initiative that could prompt the local popular music in a sense of fostering and enabling these artists to take flights beyond the limits of the state. This whole process, however, did not occur without producing their representational struggles that sought to legitimize the practices and protagonisms that each of these artists sought to impress upon themselves in the local scenario. Such struggles were part of what constituted the song as a recognized cultural expression in Teresina, especially through speeches conveyed mainly in the press. The contrasts and clashes between the regional and the international, between tradition and modernity, between urban and rural, as well as the desire for recognition in the great visibility circuits of Brazilian culture, present in criticism and journalistic articles, public musical controversies. and phonographic productions were at the center of these struggles and were the notes that made up the chord and the choir of voices of what I called here the modern Piaui popular song.